Convergence rate to singular steady states in a semilinear parabolic equation. (January 2016) - Hoshino, Masaki; Yanagida, Eiji
Abstract: We study the asymptotic behavior of singular solutions of a semilinear parabolic equation. Our aim is to determine a convergence rate to singular steady states, and to derive a universal lower bound of the convergence rate which implies the optimality of the convergence rate. Proofs are given by using a super- and subsolution method based on matched asymptotic expansion.